Os desafios para a execução da estratégia organizacional: uma análise de empresas de TI no Rio Grande do Sul - Franke, Allan Caberlon (Universidade do Vale do Rio dos Sinos, 2015)
The objective of this research is to verify if strategy planning or execution is more relevant to organizations seeking performance considering the opinions of this study subjects, identify which gaps exist on strategy execution and discuss which factors help or hinder execution. These objectives were developed considering information technology (IT) companies located in the state of Rio Grande do Sul (RS). To answer these objectives the tools used were interviews with IT companies executives located in RS and surveys were also sent to these companies. Documental research were also conducted using the database of Associação das Empresas Brasileiras de Software e Serviços de Informática - Regional do RS (ASSESPRO-RS) which is the association of brazilian software and IT services companies, seeking to identify the companies needed to characterize this market, as well as bibliographic research to further enrich the research. Regarding the importance of strategy execution, results show that it has a bigger impact on financial performance than strategy planning, this seems to be explained by companies having less difficulty when planning strategy. Both the survey respondents and the interviewed executives identified ineffective communication regarding of the strategy to all the levels of the organization and ineffective monitoring as organizational gaps. These findings have similarities with previous research on the subject that used the same survey as the one used on this research. The factors that were identified as the most important for aiding execution, considering survey results and interviewed executives, were performance monitoring, leadership development, strategy communication and developing an action plan. These results can suggest that strategy execution is aided specially by the organization capacity of guaranteeing that all individuals know the strategy, inform these individuals what has to be done to make the strategy happen and make adjustments considering the information available on the indicators.
Keywords: Execução; Execução da estratégia; Gap estratégia execução; Implementação da estratégia; Barreiras execução estratégia; Factors strategy execution; Strategy performance gap; Strategy execution; Strategy implementation; ACCNPQ::Ciências Sociais Aplicadas::Administração